Konsep Diri Pada Mahasiswa Perempuan Yang Mengalami Obesitas di Institut Agama Islam Negeri (IAIN) Kediri (Self-Concept of Female Students Experiencing Obesity at the State Islamic Institute (IAIN) of Kediri) - Kurniasari, Sandy; Suminta, Rini Risnawita; Sunarno (Program Studi Psikologi Islam (IAIN) Kediri, 2024)
Obesity can decrease the quality of life for those affected. The issue of obesity in female students is not only related to their physical condition but also affects their psychological well-being. Meanwhile, self-concept encompasses an individual's mental representation of themselves, including both physical and psychological aspects. The aim of this study is to understand the self-concept of female students experiencing obesity and the factors influencing it. This research employs a qualitative method with a phenomenological approach. Data were obtained through interviews with five female student subjects experiencing obesity. Subjects were selected using purposive sampling technique. The criteria for subjects in this study were active female students at the State Islamic Institute (IAIN) of Kediri, unmarried, with a body mass index (BMI) classification indicating obesity (BMI > 25.0 according to WHO). The results of this study are as follows: (1) The self-concept of female students experiencing obesity at the State Islamic Institute (IAIN) of Kediri is that they can describe their current physical and psychological conditions. Slimness is considered the beauty standard in their environment, although the subjects have their own beauty standards and make efforts to achieve them. Obesity does not hinder them in carrying out daily activities but affects their health. Female students experiencing obesity receive negative treatment and comments from their surroundings. They feel sad, regretful, self-blaming, and self-loathing about having an obese body. They also experience anxiety related to their health and lack confidence when looking in the mirror. In interactions, they may appear relaxed or embarrassed, but they still fulfill their daily roles effectively. (2) Factors influencing the self-concept of female students experiencing obesity include body shape, nicknames, unsuccessful weight loss attempts, and social support.